Do Demographics Matter for African Child Poverty? - Batana, Yele M. (World Bank, Washington, DC, 2018)
The effect of demographics on poverty measurement based on per capita consumption is well known. The size and composition of the household can affect the well-being of everyone in the household, with respect to total consumption within that household. Failure to address this issue may often lead to an underestimation or overestimation of poverty, especially for children. Many studies have tried to address the issue, using the generic approach of equivalence scales. However, the choice of scale is controversial and may lead to comparability problems between countries because of the different demographic structures and choice of the pivot household for establishing the per capita poverty line. Based on the World Bank's African poverty database, this study estimates poverty rates for African children using the new international poverty line of $1.90 a day defined in terms of 2011 purchasing power parity. The equivalence scales approach (Food and Agriculture Organization/World Health Organization) is used with the adjustment suggested by Deaton after the identification of the pivot household, which is defined as the household whose per capita consumption is around the international poverty line. This study shows that taking account of demographics results in downward adjustments of child poverty, adult poverty, and child-adult poverty gaps. Moreover, breakdowns by country show that poverty may vary significantly depending on demographics, which may cause some reranking when comparing poverty between African countries. Finally, sensitivity analyses reveal that child poverty is not sensitive to the child discount factor, unlike adult poverty, but, overall, taking account of demographics is helpful for better identifying poor children.